Vulnerability to Trends to Thinking Radically Among High School Students in Sukabumi District - Muhammad Nur imanulyaqin; Elly Malihah; Yadi Ruyadi (Jurnal Paedagogy, 2024)
This study aims to reveal the vulnerability of high school students in Sukabumi district to the tendency of their approval of some of the initial ideological surfaces of radical groups in Indonesia so that it is hoped that when the potential vulnerability of this agreement is known, detection and mapping of the characteristics of thinking can be carried out students there. The approach used in this study was quantitative, using a survey method with a sample of 692 students. The data collection technique used was a questionnaire, which the researcher saves in a Google form, and the data analysis technique used is the descriptive statistic technique. The result showed that, in general, the vulnerability of their thinking tendencies is divided into two types: the vulnerability to religious radicalism and the vulnerability to non-religious radicalism. In the type of vulnerability to religious radicalism it is further divided into three types where the first is the tendency of radical terrorism thinking in the name of religion, with 100 respondents, or 14.45% had a low category, 491 respondents or 70.95% being in the moderate category, and 101 respondents or 14.59 % in the high category. Second, the type of vulnerability to the tendency to think radically in the aspect of thinking where 77 students or 11.12%, have a low category, 498 students or 71.96%, are in the medium category. As many as 117 students, or 16.90%, are in the high category. In the third type, namely vulnerability to violent radical thinking tendencies, 76 students or 10.98%, are in a low category, 508 students, or 73.41%, are in the medium category, and 108 students or 15.60%, are in the high category. Meanwhile, in the type of non-religious radicalism, the vulnerability of thinking shows that 97 students or 14.01% are in a low category, 488 students or 70.52%, are in the medium category, and as many as 107 students or 15.46%, are in the high category.